Strategi Komunikasi Sosialisasi Pelayanan Kesehatan Hewan di Bone Bolango: Strategi Komunikasi Sosialisasi Pelayanan Kesehatan Hewan di Bone Bolango - Minarni Tolapa; Ariandi Saputra; Vincent Laude (Communication and Islamic Broadcasting Studies IAIN Parepare, 2026)
Animal health service programs require communication that can reach livestock farmers, clarify service procedures, and encourage local participation. This study analyzes the communication strategies used by the Food Security and Agriculture Office of Bone Bolango Regency in socializing animal health services. A descriptive qualitative approach was employed, with informants selected purposively according to their relevance to the research focus. Data were collected through observation, interviews, and documentation, then interpreted using a development communication perspective. The findings identify three main strategies. The media-based strategy uses Facebook, WhatsApp, and billboards to expand information reach. The instructional strategy is implemented through counseling and training activities conducted two to three times a year to strengthen farmers’ understanding. The participatory strategy involves village officials and community members in disseminating information. These strategies operate complementarily by building reach, understanding, and local involvement. The study emphasizes that effective public service communication depends on integrating channels, learning activities, and community networks rather than relying on a single medium.